Pengaruh Gambaran Radiografi Thoraks dan Trombosit dengan Keparahan Pasien Covid-19 - Fauzan Rahman Latama; Sadeli Masria; Yani Triyani (Bandung Conference Series: Medical Science, 2023)
Abstract. Coronavirus Disease 2019 (COVID-19) is a disease caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). There is some way to diagnose Covid-19 patient, one of which is thrombocyte and imaging of Chest X-ray. The purpose of this study is to determine the relationship between thrombocyte value and imaging of Chest x-ray in severity of Covid-19 patients. This research uses total sampling method. The subject of this study was medical records of patients diagnosed Covid-19 who were hospitalized at Al-Islam Hospiital Bandung for the time period between January-March 2021. Data analysis used the chi square test. The result of this study showed that thrombocyte value has no significant relationship with severity in Covid-19 patients (p-value = 0.392) and Chest x-ray imaging has significant relationship with severity in Covid-19 Patients (p-value = 0.0001.). This study concluded that thrombocyte value has no significant relationshop with severity in Covid-19 patients and chest x-ray imaging has significant relationship with severity in Covid-19 patients. Abstrak. Coronavirus disease 2019 (Covid-19) merupakan penyakit infeksi virus yang penyebabnya adalah virus yang bernama severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Ada berbagai cara untuk melakukan diagnosis pasien Covid-19, seperti menggunakan jumlah trombosit dan gambaran Radiografi thoraks. Tujuan penelitian ini untuk mengetahui hubungan jumlah trombosit dan gambaran radiografi thoraks dengan tingkat keparahan pada pasien Covid-19. Penelitian ini menggunakan metode total sampling. Subjek penelitian ini adalah rekam medis pasien terkonfirmasi Covid-19 yang dirawat inap di Rumah Sakit Al-Islam Bandung periode Januari-Maret 2021. Analisis data menggunakan uji chi square. Hasil dari penelitian ini menyatakan nilai trombosit dengan tingkat keparahan pasien Covid-19 tidak memiliki hubungan (p-value = 0.392) dan menyatakan gambaran chest x-ray dengan tingkat keparahan pasien Covid-19 memiliki hubungan (p-value = 0.0001). kesimpulan dari penelitian ini adalah nilai trombosit dan tingkat keparahan pasien Covid-19 tidak memiliki hubungan dan gambaran radiografi toraks memiliki hubungan dengan tingkat keparahan pasien Covid-19.